Corticosteroid Injection for an Orthopedic Complaint in a Female with Gestational Diabetes - Palee Myrex; Lorie Harper; Sara Gould (SpringerOpen, 2018)
Abstract A female with gestational diabetes presented with hip pain characteristic of meralgia paresthetica and trochanteric bursitis. She had similar episodes prior to pregnancy that were treated successfully with non-steroidal anti-inflammatory drugs (NSAIDs) and corticosteroid injections. However, NSAID use during pregnancy poses risks to the fetus and corticosteroids carry a risk of hyperglycemia, especially in those with diabetes. Unfortunately, all attempts made to treat her conservatively failed to improve her symptoms. The use of antenatal corticosteroids as an intervention for preterm labor has been documented, but to our knowledge, there are no published reports of corticosteroid injections for orthopedic complaints in someone with gestational diabetes. Review of her glucose log showed well-controlled levels, and subsequently, a corticosteroid injection was administered. Blood glucose levels were monitored for the next 48 h, and all measurements were within normal limits. The patient's symptoms resolved, and she went on to vaginally deliver a healthy term infant without complications, suggesting that gestational diabetes should not be used as absolute criteria to withhold corticosteroid injections for orthopedic complaints.